2017
DOI: 10.1186/s12957-017-1196-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiofrequency ablation versus other ablating techniques on hepatocellular carcinomas: a systematic review and meta-analysis

Abstract: BackgroundPercutaneous ablation has quickly arisen as one of the important alternative treatments for hepatocellular carcinoma (HCC). We aimed to compare the therapeutic effects of radiofrequency ablation (RFA) and other ablative techniques on HCCs.MethodsDatabases were searched to identify literature on complete tumor ablation (CTA), overall survival (OS), local tumor recurrence (LTR), and complications of RFA in the treatment of HCC, compared with those of microwave ablation (MWA), percutaneous ethanol injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 34 publications
5
90
1
Order By: Relevance
“…The use of MWA has nonetheless been widely questioned because of the potentially higher risk of major biliary damage associated with the greater amount of energy delivered. That said, no differences emerged in the major complication rates between MWA and RFA in a single‐institution study, or a recent systematic literature review . In the present large series, VL MWA was associated with an overall 30.8% morbidity rate.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The use of MWA has nonetheless been widely questioned because of the potentially higher risk of major biliary damage associated with the greater amount of energy delivered. That said, no differences emerged in the major complication rates between MWA and RFA in a single‐institution study, or a recent systematic literature review . In the present large series, VL MWA was associated with an overall 30.8% morbidity rate.…”
Section: Discussionmentioning
confidence: 49%
“…That said, no differences emerged in the major complication rates between MWA and RFA in a single-institution study, 32 or a recent systematic literature review. 33 In the present large series, VL MWA was associated with an overall 30.8% morbidity rate. Our results broadly overlap with recent experiences involving RFA, particularly as concerns the reported rate of major complications (2%), 9 which is lower than in earlier reports.…”
Section: Safety Profilementioning
confidence: 50%
“…Ablation therapy can also improve the patient's immune ability, and kill small lesions that have not been discovered by medical imaging. Several ablation methods have their own advantages, and the safety of laser and percutaneous ethanol injection is the highest in the treatment of liver cancer . They can be the application in high‐risk areas for protecting the important organs.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with RFA, identical effects were found in MWA and cryoablation. 19 It showed that RFA appeared more effective, but with a higher rate of complications. This differs from the findings presented here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation